The Early Growth of Maize Under Waterlogging Stress, as Measured by Growth, Biochemical, and Molecular Characteristics - Ana Nikolić; Manja Božić; Nikola Delić; Ksenija Marković; Marija Milivojević; Zoran Čamdžija; Dragana Ignjatović Micić (Biology)
An effective strategy to address the impacts of climate change on maize involves early planting, which mitigates drought stress during critical growth phases, preventing yield reductions. The research assessed two maize inbred lines (sensitive and tolerant to low temperature) under conditions of waterlogging stress. This is crucial since early sowing often faces both low temperatures and heavy rain. Morphological, biochemical, and molecular responses were recorded after 24 h, 72 h, and 7 days of stress during the growth stage of 5-day-old seedlings. The findings indicated a more pronounced decline in all morphological characteristics in the sensitive line. Both genotypes displayed an increased root-to-shoot ratio, suggesting that the shoots deteriorate more rapidly than the roots. Physiological evaluations demonstrated that the tolerant line was more effective in managing ROS levels compared to the sensitive line. The involvement of H2O2 in aerenchyma formation implies that the decreased POD activity and elevated MDA levels observed after seven days may be associated with aerenchyma development in the tolerant line. Genes essential for PSII function revealed that waterlogging adversely affected photosynthesis in the sensitive genotype. In summary, the low-temperature tolerant genotype exhibited significant resilience to waterlogging, indicating potential interaction between the pathways governing these two abiotic stressors.